VOCABULARY OF CLOTHES, FOOTWEAR AND ACCESSORIES AS AN OBJECT OF SCIENTIFIC STUDY - Бобер, Тетяна (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
The study of the lexical-semantic system of dialects is relevant in Ukrainian linguistics. The thematic group of vocabulary to describe clothes, footwear and accessories, which reflects historically determined cultural, social and temporal changes in the language, is of particular interest. Purpose. The representation of lexical unit repertoire of some household vocabulary gives an opportunity to trace the repertoire dynamics of the thematic vocabulary group to describe clothes, footwear and accessories in modern Mid-Upper Dnieper dialects. Methods. To achieve the goal set, the following methods of scientific investigation are applied: expedition (to fix dialectal material), description (to register and systematize material), comparative analysis (to compare the names of clothes, footwear and accessories at different time slices). Results. The repertoire of lexical units is partially kept in the speech of older dialect speakers. Due to the cultural social changes and deactivating part of the realities, some lexemes are in the passive vocabulary of speakers. There is only partial information about some names of clothes, footwear and accessories or their semantics is modified. Some part of domain names has already been archaism. Originality. A new factual material showing changes in the linguistic consciousness of dialect speakers and enabling the investigation of nominative processes and shifts in the semantic structure of lexemes to describe clothes, footwear and accessories is recorded for the first time in the modern Mid-Upper Dnieper dialects by expeditions. The obtained data complete the information on the vocabulary of the Mid-Upper Dnieper dialect. Conclusion. The conducted research confirms the preservation of the main repertoire of the thematic vocabulary group to describe clothes, footwear and accessories, a significant part of which is in the active use of dialect speakers. At the same time, the names of ancient traditional clothes and footwear have become archaisms due to the deactivation of realities. The task of future studies is to add to the repertoire of dialectal units, to structure the material and to study the principles of the nomination in detail.